EFIKASI DIRI DAN KEMATANGAN KARIR PADA REMAJA - Quroyzhin Kartika Rini; Mohammad Dimas Atmaja (Arjwa: Jurnal Psikologi, 2023)
Career maturity in adolescents can assist in planning and determining the desired career choices according to their interests and abilities. One of the important things to be able to increase career maturity is self-efficacy. This study aims to empirically determine the effect of self-efficacy on career maturity in adolescents. The method used in this study was quantitative research with 158 respondents, aged 17-21 years, and the sampling technique used was incidental sampling. Measuring tools used in this study are career maturity scale and self-efficacy scale. Based on the results of data analysis using simple linear regression technique, it was found that there was an effect of self-efficacy on career maturity in adolescents, with an R squared value of 0.192 and a significance value of p<0.01. These results indicate that self-efficacy contributes 19.2% to career maturity in adolescents, while 90.8% is influenced by other factors that not examined in this study.